Ancient origin and recent range expansion of the maize weevil Sitophilus zeamais, and its genealogical relationship to the rice weevil S. oryzae - Corrêa, A. S.; Vinson, C. C.; Braga, L. S.; Guedes, R. N. C.; Oliveira, L. O. de (Bulletin of Entomological Research, 2017)
Archeological records attest the early association of Sitophilus with stored cereals from the beginning of agriculture on Asia. The maize weevil (Sitophilus zeamais) became particularly damaging to maize, a cereal crop domesticated on Mesoamerica. We investigated the late evolutionary history of the maize weevil to gain insights on its origin, timing of association with maize, and genealogical relationship to the almost morphologically indistinguishable rice weevil (Sitophilus oryzae). Two mitochondrial genes (cytochrome oxidase subunit I and cytochrome oxidase subunit II) and the nuclear ribosomal gene region were partially sequenced. Analyses showed that the maize weevil shared no haplotypes with the rice weevil; instead, each species exhibited distinct mitogroups and ribogroups. The two weevil species likely split about 8.7 million years ago (95% highest posterior density: 4.0–15.0). Microsatellite data analyses sorted the 309 specimens from 15 populations of the maize weevil into three genotypic groups, which displayed low genetic differentiation and widespread occurrence worldwide. The maize weevil and the rice weevil are each a distinct species; both of which emerged prior to the onset of agriculture. The maize–maize weevil association took place after maize became widespread as a global crop. The maize weevil populations lack spatial genetic structure at the regional, continental, and intercontinental scales.
Keywords: Cereal; Maize weevil; Phylogeography; Population genetics; SSR markers; Stored grain pest